2016
DOI: 10.1111/ped.13087
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin‐B immobilized column–direct hemoperfusion for adolescent toxic shock syndrome

Abstract: Toxic shock syndrome (TSS) is a critical illness associated with toxin from Staphylococcus aureus. Despite recent advances in critical care, mortality remains high and additional effective therapy is required. We report an adolescent case of TSS successfully treated with direct hemoperfusion using polymyxin-B immobilized fiber (PMX-DHP). The patient with spina bifida also had ischial pressure ulcer, and developed TSS associated with methicillin-resistant S. aureus. Despite conventional treatment, the patient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Alternative treatment was urgently required to maintain life. On hospital day 3, we decided to perform PMX‐DHP to suppress the cytokine storm (Figure ; reprinted from Suzuki et al based on the reported effectiveness of PMX‐DHP for sepsis due to Gram‐positive bacteria . Immediately after the first PMX‐DHP session, he opened his eyes spontaneously and his consciousness level dramatically improved (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative treatment was urgently required to maintain life. On hospital day 3, we decided to perform PMX‐DHP to suppress the cytokine storm (Figure ; reprinted from Suzuki et al based on the reported effectiveness of PMX‐DHP for sepsis due to Gram‐positive bacteria . Immediately after the first PMX‐DHP session, he opened his eyes spontaneously and his consciousness level dramatically improved (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of our 10 patients were identified to have Gram‐positive bacteria, which do not have lipopolysaccharide. However, PMX fibers were reported to adsorb LTA, and PMX‐DHP is effective for septic shock due to Gram‐positive bacteria …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorptive therapies have been utilized mostly for hyperinflammatory syndromes (hemophagocytic lymphohystiocitosis, macrophage activation syndrome) or toxin-mediated infections manifesting as SIRS/septic shock. Two clinical reports from Japan on non ECMO neonates with sepsis/toxic shock highlight the potential adoption of these techniques on ECMO (70,71). Similarly, non ECMO studies on adults with septic shock treated with HA330 adsorption cylinder showed improved hemodynamic parameters and decreased mortality (72).…”
Section: Role Of Adjunctive Extracorporeal Therapiesmentioning
confidence: 99%
“…PMX-HP might also attenuate pro-apoptotic plasma activity on septic renal tubular cells (17). Beneficial effects concerning GPC infection have scarcely been reported while the PMX-HP treatment strategy for severe toxic shock syndrome in children has also been proposed (18).…”
mentioning
confidence: 99%